1999
DOI: 10.1076/brhm.30.4.424.1416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Light Regimes on Pre-Adult Fitness in Drosophila melanogaster Populations Reared in Constant Light for over Six Hundred Generations

Abstract: Egg to eclosion development time and survivorship were assayed on four laboratory populations of Drosophila melanogaster that had been reared for over 600 generations in continuous light (LL) and constant temperature. The assays were performed in three environments: continuous light (LL), periodically varying light/dark cycles (LD 12:12 hr), and continuous darkness (DD). Development time in LL was significantly less than that in LD, which, in turn, was significantly less than that in DD, whereas survivorship d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…On the other hand, environments such as DD and LD cycles, wherein eclosion is rhythmic, the interaction between developmental state and eclosion clock would determine the duration of pre-adult development, and the developmental time would then be expected to be greater than those under LL. In a previous study on four Drosophila populations maintained under LL (JB1..4), the ancestral populations of the flies used in the present study, we had reported shortest development time under LL regime, followed by LD 12:12 h, and DD [14]. In the present study too development time was shortest under LL, followed by T20 , DD, and T24 and T28 , in that order.…”
Section: Discussionsupporting
confidence: 66%
“…On the other hand, environments such as DD and LD cycles, wherein eclosion is rhythmic, the interaction between developmental state and eclosion clock would determine the duration of pre-adult development, and the developmental time would then be expected to be greater than those under LL. In a previous study on four Drosophila populations maintained under LL (JB1..4), the ancestral populations of the flies used in the present study, we had reported shortest development time under LL regime, followed by LD 12:12 h, and DD [14]. In the present study too development time was shortest under LL, followed by T20 , DD, and T24 and T28 , in that order.…”
Section: Discussionsupporting
confidence: 66%
“…Under DD where circadian clocks free‐run with endogenous periodicity close to 24 h, time‐to‐emergence is likely to be determined by the interaction between developmental states of the fly and circadian gating (Qui & Hardin, ), and therefore time‐to‐emergence would be expected to be comparable to that in T24 . Indeed, time‐to‐emergence is found to be shorter under LL compared with T24 and DD (Sheeba et al ., ; Paranjpe et al ., ; Figs. and ).…”
Section: Discussionmentioning
confidence: 99%
“…Circadian ( circa = about ; dies = a day ) clocks with near 24‐h periodicities regulate behavioral and metabolic processes in a wide variety of organisms (Saunders, ; Dunlap et al ., ). In insects including fruit flies Drosophila melanogaster , these clocks have also been implicated in the regulation of life‐history traits such as preadult development time and adult lifespan (Kyriacou et al ., ; Miyatake, , ; Shimizu et al ., ; Klarsfeld & Rouyer, ; Sheeba et al ., ; Paranjpe et al ., ; Takahashi et al ., ; Yadav & Sharma, 2013, 2014). It is believed that preadult development time of flies with faster circadian clocks is shorter than those with slower clocks.…”
Section: Introductionmentioning
confidence: 99%
“…In all these examples, LNS experiments will be selecting on lines that at least initially suffer laboratory induced (if inadvertently so) anomalies or even pathologies, such that the resulting evolutionary trajectories might differ from those of healthy lines. To be sure, lines evolving under constant photoperiod may adapt to such conditions (Sheeba et al 1999), but whether those lines can serve as reliable models for "natural" organisms is uncertain.…”
Section: Laboratory Environments Are Too Stressfulmentioning
confidence: 99%